India’s Unbalanced Urban Growth: An Appraisal of Trends and Policies - Purva Sharma (Journal of Global Initiatives, 2018)
India is considered as a low-level urbanized country. However, the country has experienced a sharp increase in the number of towns and peri-urban areas during the last decade. Despite India’s efforts in planned development, the urban sector has generally remained unplanned and chaotic. It appears that policy interventions have not been able to achieve the desired goals and needs of the urban sector fully. This paper examines the urban policy measures taken since independence and highlights the inadequacies and dilemmas in the urban context of India. This analysis shows how metropolitan areas are spreading outwards due to shifts in population and economic activities from city cores to the peripheries and considers the policy implications of such trends.